Analysis of agriculture based sector in regional development of Gowa Regency. Issue 3 (July 2021) - Mahyuddin,; Arsyad, M; Darma, R; Fahmid, M; Fudjaja, L; Rukka, R M; Miftahulmawaddah,
Abstract: Agriculture sector as one of the potential economic sectors in contributing to national economic growth and development, both in terms of income and labor absorption. Analysis of the determination of the base sector is needed as the basis for the formulation of economic development policy patterns in Gowa Regency in the future, so that economic development policies can be directed to move those sectors. This research aims to analyze the agricultural sector and other sectors that become the basis in the regional economy in Gowa Regency. This study used secondary data in the form of Gross Regional Domestic Product (GDP) data and gdp growth rate of Gowa Regency and South Sulawesi Province in 2012-2016 and analyzed using Location Quotient, Shift Share and Klassen Typology methods. The results concluded that the Agriculture, Forestry, and Fisheries Sector is one of the economic sectors that is the base in Gowa Regency, but is a 'developed but depressed (stagnant sector) sector' due to the slowing growth rate every year.